Example 60.19.1. Suppose that $A_*$ is any cosimplicial ring. Consider the cosimplicial module $M_*$ defined by the rule

$M_ n = \bigoplus \nolimits _{i = 0, ..., n} A_ n e_ i$

For a map $f : [n] \to [m]$ define $M_*(f) : M_ n \to M_ m$ to be the unique $A_*(f)$-linear map which maps $e_ i$ to $e_{f(i)}$. We claim the identity on $M_*$ is homotopic to $0$. Namely, a homotopy is given by a map of cosimplicial modules

$h : M_* \longrightarrow \mathop{\mathrm{Hom}}\nolimits (\Delta , M_*)$

see Section 60.16. For $j \in \{ 0, \ldots , n + 1\}$ we let $\alpha ^ n_ j : [n] \to $ be the map defined by $\alpha ^ n_ j(i) = 0 \Leftrightarrow i < j$. Then $\Delta _ n = \{ \alpha ^ n_0, \ldots , \alpha ^ n_{n + 1}\}$ and correspondingly $\mathop{\mathrm{Hom}}\nolimits (\Delta , M_*)_ n = \prod _{j = 0, \ldots , n + 1} M_ n$, see Simplicial, Sections 14.26 and 14.28. Instead of using this product representation, we think of an element in $\mathop{\mathrm{Hom}}\nolimits (\Delta , M_*)_ n$ as a function $\Delta _ n \to M_ n$. Using this notation, we define $h$ in degree $n$ by the rule

$h_ n(e_ i)(\alpha ^ n_ j) = \left\{ \begin{matrix} e_{i} & \text{if} & i < j \\ 0 & \text{else} \end{matrix} \right.$

We first check $h$ is a morphism of cosimplicial modules. Namely, for $f : [n] \to [m]$ we will show that

60.19.1.1
\begin{equation} \label{crystalline-equation-cosimplicial-morphism} h_ m \circ M_*(f) = \mathop{\mathrm{Hom}}\nolimits (\Delta , M_*)(f) \circ h_ n \end{equation}

The left hand side of (60.19.1.1) evaluated at $e_ i$ and then in turn evaluated at $\alpha ^ m_ j$ is

$h_ m(e_{f(i)})(\alpha ^ m_ j) = \left\{ \begin{matrix} e_{f(i)} & \text{if} & f(i) < j \\ 0 & \text{else} \end{matrix} \right.$

Note that $\alpha ^ m_ j \circ f = \alpha ^ n_{j'}$ where $0 \leq j' \leq n + 1$ is the unique index such that $f(i) < j$ if and only if $i < j'$. Thus the right hand side of (60.19.1.1) evaluated at $e_ i$ and then in turn evaluated at $\alpha ^ m_ j$ is

$M_*(f)(h_ n(e_ i)(\alpha ^ m_ j \circ f) = M_*(f)(h_ n(e_ i)(\alpha ^ n_{j'})) = \left\{ \begin{matrix} e_{f(i)} & \text{if} & i < j' \\ 0 & \text{else} \end{matrix} \right.$

It follows from our description of $j'$ that the two answers are equal. Hence $h$ is a map of cosimplicial modules. Let $0 : \Delta  \to \Delta $ and $1 : \Delta  \to \Delta $ be the obvious maps, and denote $ev_0, ev_1 : \mathop{\mathrm{Hom}}\nolimits (\Delta , M_*) \to M_*$ the corresponding evaluation maps. The reader verifies readily that the compositions

$ev_0 \circ h, ev_1 \circ h : M_* \longrightarrow M_*$

are $0$ and $1$ respectively, whence $h$ is the desired homotopy between $0$ and $1$.

In your comment you can use Markdown and LaTeX style mathematics (enclose it like $\pi$). A preview option is available if you wish to see how it works out (just click on the eye in the toolbar).